Spin resonance studies of the quasi-one-dimensional Heisenberg antiferromagnet Cs2CuCl4 - Schrama, J; Ardavan, A; Semeno, A; Gee, P; Rzepniewski, E; Suto, J; Coldea, R; Singleton, J; Goy, P (1998)
Measurements of the magnetic-field dependent millimetre-wave response of Cs2CuCl4, a quasi-one-dimensional Heisenberg antiferromagnet, are presented. The evolution of the electron spin resonance between high temperatures (the paramagnetic regime) and temperatures below T-N, at which there is an onset of long-range magnetic order (the antiferromagnetic regime), is studied for a range of crystal orientations. The magneto-optical data suggest that there is an onset of local magnetic order at temperatures considerably higher than T-N as determined from neutron scattering measurements, and that the evolution towards a long-range ordered state is gradual. A phenomenological model that describes the general features is suggested. (C) 1998 Elsevier Science B.V. All rights reserved.